Longitudinal Form Factors and Quadrupole Moments of 22,26Na Isotopes with Different Interactions - Raheem, Sh. K.; Dakhil, Z. A. (Iraqi Journal of Science, 2022)
The longitudinal electron scattering form factors and the electric quadrupole moments are calculated for the states with Jπ T= 3+0 (ground state) and 1+ 0 (583keV excited state) of 22Na and Jπ T= 3+2 (ground state) of 26Na. Shell model calculations are based on USDA, USDB and Wildenthal interactions. The exact center of mass correction is included in Born approximation picture to generate the longitudinal form factors. The core polarization (CP) effect with the values of effective nucleon charges ep=1.35, en= 0.35, with Bohr Mottelson formula gave a good agreement with the measured electric quadrupole moments. The structure of the nuclei under consideration shows that the 1d5/2 orbit is dominant configuration for 22Na, and 2s1/2 orbit for 26Na.